Penggunaan Bahasa Engghi Bhunten untuk Pelestarian Bahasa Madura di Pondok Pesantren Putri Al Maimunah: The Use of Engghi Bhunten Language for the Preservation of the Madurese Language at Pondok Pesantren Putri Al Maimunah - Rosyadah, Tsamrotur; Nurhadi, Ali; Mukminin, Amirul (Information Technology and Science(ITScience), 2025)
Engghi Bhunten is the highest level of Madurese speech, reflecting the highest level of politeness and respect. However, its use is now threatened by the influence of globalization and modernization. At the Al-Maimunah Girls' Islamic Boarding School, although the majority of students are Madurese, they rarely use Engghi Bhunten in their daily communication. This study aims to analyze the use of Engghi Bhunten as an effort to preserve the Madurese language within the girls' Islamic boarding school environment. This qualitative research, with a descriptive and interpretive design, was conducted at the Al-Maimunah Girls' Islamic Boarding School in Kembang Jeruk Village, Sampang Regency, East Java. Participants were selected purposively, consisting of the head of the boarding school, female teachers, and students. Data were collected through non-participant observation, semi-structured interviews, and documentation. Data validity was ensured through the triangulation of sources and techniques, while data analysis involved reduction, presentation, and drawing conclusions. The use of Engghi Bhunten at the Al-Maimunah Girls' Islamic Boarding School is systematically integrated into all student activities and has a significant impact on preserving the Madurese language. Internal factors that support this are the students' awareness of maintaining good manners, while external factors include the boarding school's rules, the role models of female teachers and senior students, and the consistency of the boarding school environment. The impact is evident in the students' increased understanding of the levels of politeness, language rules, and the use of vocabulary in context, enabling them to become more polite, confident, and skilled in speaking Madurese. The practice of using Engghi Bhunten not only improves students' linguistic competence but also fosters a polite and cultured character, while making them active agents in preserving the Madurese language. The boarding school plays an effective role as a space for habituating regional language preservation through the integration of cultural and religious values in everyday communication.